2014
DOI: 10.1007/s11596-014-1351-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study of electro-acupuncture treatment with different intensities for functional constipation patients

Abstract: Functional constipation (FC) is a common functional bowel disorder disease that affects life quality of a large number of people. This study aimed to explore the impact of different intensities of electro-acupuncture (EA) treatment for FC patients. Totally, 111 patients with FC meeting the Rome III criteria were randomly assigned to different intensities of EA groups (low and high intensity of EA groups) and medicine-controlled (MC) group. In EA groups, patients were treated with EA at quchi (LI11) and shangju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Tomita [ 40 ] found that STC patients' colon had a weaker response to VIP than normal colon. Xiong et al [ 41 ] found that different frequency of electroacupuncture at Quchi point and ST36 could elevate the VIP level in serum of FC patients and relieve the symptoms. This study showed that the plasma level of VIP in FC patients was lower than that of control group, and 4-week therapy did not cause significant change.…”
Section: Discussionmentioning
confidence: 99%
“…Tomita [ 40 ] found that STC patients' colon had a weaker response to VIP than normal colon. Xiong et al [ 41 ] found that different frequency of electroacupuncture at Quchi point and ST36 could elevate the VIP level in serum of FC patients and relieve the symptoms. This study showed that the plasma level of VIP in FC patients was lower than that of control group, and 4-week therapy did not cause significant change.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous IFC studies, 13 , 31 the electrodes were unambiguously positioned on the belly or belly and back; unlike these studies, the positions in our study were determined definitely according to acupoint theory. However, different acupoints were also used in some other research for patients with constipation 11 , 32 , 33 ; for example, the He-Sea points (Zusanli, ST36; Shangjuxu, ST37, etc). Wu et al 32 argued that He-Sea acupoint prescription is the best choice for the treatment of functional constipation in comparison with other acupoints.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 10 In recent years, acupuncture and electroacupuncture have been confirmed as effective in the management of GI motility disorders, such as chronic treatment-resistant constipation. 11 , 12 Compared with traditional acupuncture and electrical acupuncture, transcutaneous acupoint interferential current (IFC) therapy has the advantage of being noninvasive as well as amenable to adjustability of stimulation frequency and intensity objectively and quantifiably; therefore, it is increasingly being applied in various GI diseases. 13 - 16 In this study, we assess transcutaneous acupoint IFC stimulation with pad electrodes on the belly (acupoints ST25 and RN12) in cancer pain patients with OIC, compared with oral lactulose administration, to observe its efficacy and safety in this population.…”
Section: Introductionmentioning
confidence: 99%
“…As previously noted, there has been a great deal of published research concerning the optimal frequency of EA [ 1 , 2 ]. There is also some literature regarding EA intensity effects [ 15 ]. However, to date, there is very little known about the intensity-response effect of EA, in either clinical trials or preclinical experiments.…”
Section: Discussionmentioning
confidence: 99%